The SCF/Slimb ubiquitin ligase limits centrosome amplification through degradation of SAK/PLK4. - Cunha-Ferreira, I.; Rodrigues-Martins, A.; Bento, I.; Riparbelli, M.; Zhang, W.; Laue, E.; Callaini, G.; Glover, D.M.; Bettencourt-Dias, M. (Current Biology, 2009)
Centrioles are essential for the formation of microtubule-derived structures, including cilia and centrosomes. Abnormalities in centrosome number and structure occur in many cancers and are associated with genomic instability. In most dividing animal cells, centriole formation is coordinated with DNA replication and is highly regulated such that only one daughter centriole forms close to each mother centriole. Centriole formation is triggered and dependent on a conserved kinase, SAK/PLK4. Downregulation and overexpression of SAK/PLK4 is associated with cancer in humans, mice, and flies. Here we show that centrosome amplification is normally inhibited by degradation of SAK/PK4 degradation, mediated by the SCF/Slimb ubiquitin ligase. This complex physically interacts with SAK/PLK4, and in its absence, SAK/PLK4 accumulates, leading to the striking formation of multiple daughter centrioles surrounding each mother. This interaction is mediated via a conserved Slimb binding motif in SAK/PLK4, mutations of which leads to centrosome amplification. This regulation is likely to be conserved, because knockout of the ortholog of Slimb, beta-Trcp1 in mice, also leads to centrosome amplification. Because the SCF/beta-Trcp complex plays an important role in cell-cycle progression, our results lead to new understanding of the control of centrosome number and how it may go awry in human disease.